1995
DOI: 10.1152/ajpcell.1995.269.3.c785
|View full text |Cite
|
Sign up to set email alerts
|

Maximum speed of shortening and ATPase activity in atrial and ventricular myocardia of hyperthyroid rats

Abstract: The kinetic properties of the myofibrillar system of atrial and ventricular myocardia of hyperthyroid rats were analyzed by determining ATPase activity and maximum shortening velocity. Hyperthyroidism was induced by daily subcutaneous injections of triiodothyronine (0.2 mg/kg body wt) for 2 wk. The treatment induced a marked atrial and ventricular hypertrophy and, in ventricular myocardium, an isomyosin shift toward a homogeneous V1 composition. Skinned trabeculae and purified myofibrils were prepared from atr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 27 publications
4
11
0
Order By: Relevance
“…In this study, we altered the ventricular expression of MHC, which is the molecular motor that largely determines myocyte contractile behavior, such that rat ventricles only expressed the slow ␤-MHC isoform. Consistent with previous studies (1,8,18,26), we showed that increased ␤-MHC expression significantly slowed V o and slowed the rates of cross-bridge cycling in the skinned myocardium (Figs. 3 and 4).…”
Section: Dependence Of Global LV Mechanical Performance On Mhc Isoforsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, we altered the ventricular expression of MHC, which is the molecular motor that largely determines myocyte contractile behavior, such that rat ventricles only expressed the slow ␤-MHC isoform. Consistent with previous studies (1,8,18,26), we showed that increased ␤-MHC expression significantly slowed V o and slowed the rates of cross-bridge cycling in the skinned myocardium (Figs. 3 and 4).…”
Section: Dependence Of Global LV Mechanical Performance On Mhc Isoforsupporting
confidence: 92%
“…Consistent with previous findings (1,8,18,26), we found that decreased expression of ␣-MHC significantly reduced V o , as values were approximately twofold slower in the hypothyroid myocardium compared with the euthyroid myocardium (Fig. 4).…”
Section: Effects Of Altered Mhc Expression On Mechanical Properties Osupporting
confidence: 92%
“…Tension was normalized by cross-sectional area. The unloaded maximum velocity of shortening (V max ) was extrapolated from zero loading condition according to the Maxwell model of muscle (32).…”
Section: Methodsmentioning
confidence: 99%
“…Ventricular MLC isoforms are associated with 1.2-1.8 times slower shortening velocities than atrial MLC isoforms in mouse [9,41], rat [6], and human [32]. In contrast, no clear dependence of ATPase activity on MLC isoforms was observed [6,21,41].…”
Section: Introductionmentioning
confidence: 91%